1995
DOI: 10.1073/pnas.92.10.4392
|View full text |Cite
|
Sign up to set email alerts
|

Roles of nitric oxide in tumor growth.

Abstract: A subclone of the human colon adenocarci-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
461
3
5

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 711 publications
(490 citation statements)
references
References 17 publications
21
461
3
5
Order By: Relevance
“…NO in low concentrations is known to have benign, modulating, and regulatory effects on normal mammalian and human biology. Higher concentrations of NO have been shown to be both damaging and pathologic to physiologic processes resulting in mutational events which might lead to cancer and promote progression of the tumor [6][7][8]. Our laboratory and others have shown that NO is overexpressed in many human cancers [9].…”
Section: Introductionmentioning
confidence: 79%
“…NO in low concentrations is known to have benign, modulating, and regulatory effects on normal mammalian and human biology. Higher concentrations of NO have been shown to be both damaging and pathologic to physiologic processes resulting in mutational events which might lead to cancer and promote progression of the tumor [6][7][8]. Our laboratory and others have shown that NO is overexpressed in many human cancers [9].…”
Section: Introductionmentioning
confidence: 79%
“…The dual pro-and anti-tumour action of NO was recently demonstrated to be dependent on the local concentration of the molecules (Jenkins et al, 1995). An inverse relationship between the generation of NO and the metastatic potential of a tumour was also proposed (Dong et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…B and D represent the modified Wright's stain of cells as in A and C, respectively (original magnification: A-D, x 400; E, x 200) mutagen (Mordan et al, 1993). The dual pro-and anti-tumour action of NO was recently demonstrated to be dependent on the local concentration of the molecules (Jenkins et al, 1995). An inverse relationship between the generation of NO and the metastatic potential of a tumour was also proposed (Dong et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…While NO had been shown to have anti-tumour p roperties [10], Jenkins et al [42][1995] first reporte d the surprising finding that human carcinoma cells transfected with a murine iNOS cDNA cassette (DL D-1 cells generating 20 pmol min-1 mg-1 NOS activ ity) showed increased tumour growth, rather than d ecreased growth. Using a nude mouse/xanograft mo del it was shown that growth of these NO-generatin g tumours was accompanied by increased neovascul arization.…”
Section: No and Tumour Cell Angiogenesismentioning
confidence: 99%